I-farm System: A Climate Smart Mobile Phone Based Agro-Weather Tool for Farmers in Uasin Gishu County, Kenya - Murgor, D. K.; Cheserek, G. (Africa Environmental Review Journal, 2017)
Due to climate and weather variations brought about by climate change, maize and wheat farmers have constantly faced greater risks throughout the growing season in the farming calendar in Kenya and more specifically Uasin Gishu County where this study was conducted. The unpredictable nature of the order and seasons known to farmers, rainfall onset, frequency, intensity and cessation of rainfall has led to drastic variations in yield or widespread loss of crop in Uasin Gishu County. To navigate such risks, timely access to climate information and related technologies for adaptation is essential to enable actors to anticipate long–term risks and make the appropriate adjustments. This will help farmers increase their resilience at the farm and household level. To understand these challenges, a study was conducted in Uasin Gishu County that adopted a mix of purposive, stratified and random sampling techniques to select 399 maize and wheat farmers and 12 key informants for interview. Based on the challenges of access to the required timely and downscaled climate and weather information, an innovative “I-farm system” was developed to relay timely climate information to farmers. I-farm system developed adopted the incremental build model methodology during its gradual development. The product was designed, implemented and tested incrementally to its current functional level. The findings in the study show that in Uasin Gishu County, about 60% of the farmers do not access climate and weather information although Kenya Meteorological Services produces agro-meteorological information regularly. More than 50% of the farmers further were not aware of any organization producing such information. Similarly, farmers have incurred maize and wheat crop losses due to lack of adequate rain during growing period as reported by 78.6% of the farmers. Maize and wheat yield loss due to too much rain during growing season, near harvest and harvest period was reported by 66.1% of the farmers. These findings portray a vulnerable group of farmers who have incurred losses in their farming enterprise and therefore need urgent interventional measures that include timely access and usage of climate information in farming decisions. The study findings also point to existence of a significant relationship between access and usage of information (Chi = 87.263, P < 0.001). The dissemination modes of climate information to farmers in Uasin Gishu County are largely through radio as stated by 79.8% and television affirmed by 68.4%. Almost all the farmers (96.3%) however preferred to receive or get updates (SMS Alerts) on climate and weather information through their mobile phone handsets. I-farm system developed is designed to deliver climate information to farmers via their mobile phones (SMS alerts). The system is a web based interactive application designed to inform farmers on prevailing weather patterns, advisory alerts, best practices all geared towards supporting a farmer’s decision at the farm level. The system serves farmers in rural areas where internet access is limited. Farmers on the other hand can raise issues of concern by writing an SMS back to the I-farm help desk where a staff designate can attend to queries raised by farmers. The feedback loop is important as farmers perspectives are incorporated hence ensuring ownership and sustainability of the innovation.